Plume Versus Slab-Pull: Example from the Arabian Plate - Aldaajani, Thamer Z.; Almalki, Khalid A.; Betts, Peter G. (Frontiers in Earth Science, 2021)
Mantle convection and the interaction of buoyant plumes with the lithosphere have been a significant influence on plate tectonics. Plume-lithosphere interactions have been regarded as a major driver of continental rifting, and have been linked to triple junction development and major supercontinent break-up events. There are also many extensional tectonic settings that lack evidence for a mantle plume and associated magmatism, indicating far-field plate stresses also drive plate fragmentation. The Arabian Plate is a spectacular active example where both a mantle plume and far-field plate stresses interact to drive continental break-up. Despite more than 80 years of geological research, there remains significant conjecture concerning the geodynamic processes responsible for the plate motion and the nature or onset of extension/deformation of the Arabian Plate. Complex structural patterns within the Arabian Plate have been interpreted in the context of tectonic plate movements and reorganization related to the subduction of the Tethys Oceanic plate, collision between Arabian and Eurasian plates, and the superposition of Afar plume. These interactions have accordingly resulted in different explanations or understanding of the geodynamic of the Afro-Arabian rift system. We assess the relative influence of plume versus far field influences by reviewing the current views on the concept and models of these forces and highlighting their significance and implications on Arabia. Our synthesis shows that most of the geodynamical models proposed so far are not applicable to the entire Arabian Plate and its surrounding boundaries.